2018
DOI: 10.1016/j.coisb.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Cell size control and gene expression homeostasis in single-cells

Abstract: Growth of a cell and its subsequent division into daughters is a fundamental aspect of all cellular living systems. During these processes, how do individual cells correct size aberrations so that they do not grow abnormally large or small? How do cells ensure that the concentration of essential gene products are maintained at desired levels, in spite of dynamic/stochastic changes in cell size during growth and division? Both these questions have fascinated researchers for over a century. We review how advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 59 publications
0
48
0
Order By: Relevance
“…The maintenance of homeostasis requires that cells actively control their proliferation [14,16,18]. The necessary feedback can be exerted through e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of homeostasis requires that cells actively control their proliferation [14,16,18]. The necessary feedback can be exerted through e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, tissue size may be regulated by either controlling the sizes of individual cells, or the number of constituent cells [2][3][4][5][6]. How individual cells maintain size homeostasis has been extensively studied across organisms ranging from bacteria, animal and plant cells [7][8][9][10][11][12][13][14][15][16]. Interestingly, data reveals cell-autonomous control strategies that regulate cellular growth or timing of cell-cycle events to suppress aberrant deviations in cell size around an optimal size specific to that cell type [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…S9E). S. aureus cells may contain fewer mRNAs than E. coli cells, possibly due to their smaller cell size and genome 33 , though technical differences may also affect capture. We confirmed that optimized PETRI-seq continued to capture single cells with high purity (Fig.…”
mentioning
confidence: 99%